Microsatellite Diversity and Phylogenetic Relationships among East Eurasian Bos taurus Breeds with an Emphasis on Rare and Ancient Local Cattle - Gulnara Svishcheva; Olga Babayan; Bulat Lkhasaranov; Ariuntuul Tsendsuren; Abdugani Abdurasulov; Yurii Stolpovsky (Animals, 2020)
We report the genetic analysis of 18 population samples of animals, which were taken from cattle (Bos taurus) breeds of European and Asian origins. The main strength of our study is the use of rare and ancient native cattle breeds: the Altai, Ukrainian Grey, Tagil, and Buryat ones. The cattle samples studied have different production purposes, belong to various eco-geographic regions, and consequently have distinct farming conditions. In order to clarify the genetic diversity, phylogenetic relationships and historical origin of the studied breeds, we carried out an analysis of the genetic variation of 14 high-variability microsatellite loci at 1168 genotyped animals. High levels of heterozygosity and allelic richness were identified in four of the ancient local breeds, namely the Kalmyk, Tagil, Kyrgyz native, and Buryat breeds. The greatest phylogenetic distances from a common ancestor were observed for the Yakut and Ukrainian Grey breeds, while the Tagil breed showed the smallest difference. By using clustering approaches, we found that the Altai cattle is genetically close to the Kyrgyz one. Moreover, both the Altai and Kyrgyz breeds exposed genetic divergences from other representatives of the Turano-Mongolian type and genetic relationships with the Brown Swiss and Kostroma breeds. This phenomenon can be explained by the extensive use of the Brown Swiss and Kostroma breeds in the breeding and improvement processes for the Kyrgyz breeds, which have been involved in the process of keeping the Altai cattle. Our results can be valuable for conservation and management purposes.